Rank Computation Model for Distribution Product in Fuzzy Multiple Attribute Decision Making - Syafariani R. Fenny; A. Nursikuwagus; Tono Hartono (Universitas Ahmad Dahlan, 2018)
Ranking of an activity is very important to support work effectiveness. Previous works, ranking for distribution product is used by manual process or averaging value. Problem in this research, the research should be found the effective way to rank the distribution product. This research proposes assist the ranking with a computational model based on Fuzzy Multiple Decision Making (FMADM). Getting an effective ranking, a variable in FMADM computing is required. Variables is used in this research such as number of households, number of small-scale enterprises run by households, gross domestic regional income, and economic growth rate of a region. Research completion is assisted by using self-built research methods. Research method consists of determining value of origin, determining degree of membership, determining weight of each variable, calculation of relation matrix, calculation of the preference value in each village for ranking value, and last is sorting. Operationalized FMADM is gain a result with three priorities district. Priority number one is all of district that have a rank or Vij (alternative rank) higher than 0.4. It means only 7% or 5 villages with the highest rank. Priority number second s all of district that have rank between Vij = 0.26 and Vij = 0.4. It means only 62% or 44 villages. Priority number three is district that have a rank lower than Vij = 0.26, and only 31% or 22 villages. Impact in use of FMADM, calculated in rank, is the process runs effective and dynamic with changing of weighted. User can arrange of weighted as needed.